Fact Searching in Investigative Reporting in Indonesia: A Case Study of Tempo and Gatra Magazines - Kurnia, SS; Othman, SS; Firmansyah; Kuswarno, E (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
Indexed by WOS/SCOPUS